Unlocking varve details: high-resolution sampling via freeze-melt technique - Ojala, Antti E. K.; Lapointe, Francois; Kosonen, Emilia (Springer Science and Business Media LLC, 2026)
Sediment archives, and especially annually laminated sediments, can provide valuable records of past climate and environmental change. However, the extraction of high-resolution sub-millimetre (seasonal to annual) and uncontaminated discrete subsamples from fresh sediment cores has proven difficult, time-consuming and labour-intensive. Obtaining such samples is essential for determining the relationship between measurable sediment proxies and specific climate variables, as well as for the quantification of paleoproxies. In this technical note we present a freeze-melt technique for a high-resolution subsampling of sediment sequences. This method is based on freezing and melting of fresh sediments to obtain very thin discrete subsamples. We provide details of the method and application examples using two case studies (10Be, 137Cs) with clastic-biogenic varves from lakes Nautaj & auml;rvi and Ristij & auml;rvi in Finland. We discuss the potential advantages of the method, as well as risks and limitations that need to be considered.